Tradisi Ngubel Bagi Pasangan Pengantin Dalam Pandangan Al ‘Urf Dan Kontruktivisme Sosial - Nurdin, Muhammad; Hidayat, Taufik (ISLAMITSCH FAMILIERECHT JOURNAL, 2024)
This research examines the phenomenon of the habit of eating bananas and smoking for bridal couples after the wedding ceremony in Ibul Village, West Bangka Regency, using a qualitative approach and phenomenological perspective. Through in-depth interviews and participant observation, this research aims to understand the social and cultural meaning behind these two practices. It was found that eating bananas served as a symbol of fertility and good luck, which created an emotional bond between the bridal couple and the community. Meanwhile, smoking is considered a social activity that strengthens relationships between community members, creating a space for sharing stories and traditional values.